A Peer-led Database Training Program to Improve Reference Service. Issue 1 (3rd April 2022) - Adams, Annis Lee
ABSTRACT: Librarians at a medium-sized public university library established a peer-led database training program to improve each librarian's familiarity and utilization of the Library's specialized databases. The impetus for the training program was to reduce the number of chat reference referrals to subject specialists and instead to try to answer reference questions at the point of need. A pre-training survey identified which databases should be included in the training series and invited librarians to indicate for which databases they would be willing to be the trainer. Six databases were covered over the course of the Fall 2020 semester. A post-training survey garnered feedback on how the training series was received and also included suggestions for improvement. The post-training survey results indicate the series was viewed positively. All participants learned something new during the training sessions and felt more confident using the resources demonstrated when assisting users during reference interactions and research consultations. Participants reflected on why having colleagues conduct the training sessions rather than vendors was important. Most participants wanted to continue the training program going forward.